Design a new uniform for the high school student of the University of the Philippines integrated school - Ragos, Irene C.
The study was undertaken to develop a design suitable for a uniform for the University of the Philippines Integrated School (U.P.I.S.) high school students considering comfort, safety, and other factors such as school's image, cost and fabric type. Recognizing the advantages as well as the disadvantages of the present uniform is very important when creating a new design. In this aspect of design development, the Jones technique of searching for visual inconsistencies was applied. To gather the inconsistencies of the present uniform and to get suggestions for the new design, two types of questionnaires were used. The first set of questionnaire was for the U.P.I.S fourth year high school students who have had more experience in wearing the uniform. It was composed of three parts: 1) the background information of respondent; 2) evaluation of the present uniform; and 3) suggestions for the new uniform. The second set of questionnaire was for the Clothing Technology students who were considered more knowledgeable in clothing design. The questionnaire was divided into three parts: 1) studying the present uniform with the aid of photographs; 2) identifying the visual inconsistencies; and 3) opinions on the design details that should be included in the new uniform by sketching their ideas. The evaluation showed several inconsistencies in the present uniform in relation to style, comfort, fit, and the image they want to project. On the other hand, deleting some details such as buttons, addition of collar, waistband, patch and darts; change in color; making the skirt pleated were some of the suggestions for the new design. A design criteria was formulated and prototypes were developed. The prototype were worn by two U.P.I.S. students and evaluated by them for comfort and fit. At the same time, the researcher together with some Clothing Technology students also evaluated the prototype garments. The C.T. belonged to the same group who evaluated the present uniform. Data gathered from the evaluation of the three groups indicated that they were comfortable, safe, promote school's image in terms of color and logo, utilitarian classic in style. From the evaluation it was then concluded that the proposed uniform is very appropriate and meaningful to the U.P.I.S. students.